UPAYA PENINGKATAN KINEJA INDUSTRI KREATIF KERAJINAN MELALUI PEOPLE EQUITY DAN STRATEGI INOVASI DI KABUPATEN KONAWE - Welis Raldianingrat; Wuryanti . (Department of Management, Faculty of Economics, Universitas Islam Sutan Agung, Semarang, 2014)
Research thesis with the title of improving performance craft creative industries through people equity and innovation strategies in Konawe. This study attempts to examine the inter-relationship people equity, innovation strategy and performance craft creative industries. This type of research is survey. The population in this study is the creative craft industry as a whole is in Konawe, Southeast Sulawesi. Sampling technique in this study is nonprobabilitas with saturated sampling method and number of respondents was 96 respondents. A statistical technique used was PartialLeast Square . In this study , construct validity and reliability were tested with quantitative phases. The results showed that: ( 1 ) people equity significant positive effect on innovation strategy, ( 2 ) people equity significant positive effect on the performance of the creative craft industry and ( 3 ) innovation strategies significant positive effect on the performance of creative handicraft industry.Keywords : people equity , innovation strategy , creative craft industry performance